Perbandingan dan Kritik Naskah Kualitas Kinerja Guru Perspektif Said Ahmad Sulaiman dan La Ode Ismail Ahmad - Sherly Quraisy (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
This study aims to find out the comparison and differences in article manuscripts according to Ahmad Said Sulaiman and La Ode Ismail Ahmad. This research uses qualitative research with comparative research methods or comparisons carried out on two article manuscripts. This method uses a type of library (research library) and descriptive analysis, namely describing the article manuscript. Thus, the results of manuscript comparisons can be known for their similarities and differences after analyzing and criticizing manuscripts, because they can compare by analyzing, reading carefully and relating to the opinions of several educational figures. Based on the results of the comparison of manuscripts carried out, the content of the discussion of the manuscript of La Ode Ismail Ahmad is more specific than the manuscript of  Said Ahmad Suliaman. And the concept of teacher performance standards written by Said Ahmad Sulaiman is good to be applied in the education system. The teacher has a very important role in the study.